The Brighton Spondylodiscitis Score Does Not Accurately Predict the Need for Surgery: A Retrospective Cohort Study in New Zealand. Issue 8 (October 2022) - Hunter, Sarah; Fernando, Hasanga; Baker, Joseph F.
Study Design: Retrospective cohort study. Objectives: Despite pyogenic spondylodiscitis potentially conferring significant morbidity, there is no consensus on optimal treatment. The Brighton Spondylodiscitis Score (BSDS) was developed to identify patients who would likely fail conservative management and therefore benefit from earlier surgical intervention. In this study, we attempt external validation of the BSDS. Methods: We carried out a retrospective review of all patients treated at our institution, 2010-2016, for pyogenic spondylodiscitis. 91 met inclusion criteria and 40 progressed to require surgical intervention. The BSDS was calculated for each patient allowing stratification into low-, moderate- and high-risk groups. Calibration and discrimination was assessed with ROC curve analysis and calibration plot. Results: Area under the curve (AUC) was 0.469 (0.22-0.71) in our external validation, compared with AUC 0.83 and 0.71 (CI 0.50-0.88) in the original study and test populations respectively. Only 60% of patients in the high-risk group required surgery, 50% in the moderate, and 38% of the low indicating poor calibration and predictive accuracy. Operative intervention was not higher overall in our cohort (44% vs. 32%, p = 0.14). We found greater rates of bacteraemia, more distal infection, and more advanced MRI findings in our cohort. The incidence of spondylodiscitis in our region is higher (4/100 000/year). Conclusion: We failed to externally validate the BSDS in our population which is likely a result of unique population characteristics and the inherently variable pathology associated with spondylodiscitis. Clinicians must be cautious in adopting treatment algorithms developed in other health care systems that may comprise significantly different patient and pathogen characteristics.